2013
DOI: 10.1364/josab.30.001595
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz wave excitation from preexisting air plasma

Abstract: Terahertz (THz) wave generation process in air plasma was studied using femtosecond laser pulse pairs. The effect of preexisting air plasma was investigated using two optical geometries: collinear and orthogonal pumping geometry. When the air plasma is excited in collinear geometry, the power of the generated THz wave shows asymmetric dependence on the relative delay of these pulses. The asymmetry depends on the relative intensities of these pump pulses, and it disappears when the pulses have equal intensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…The critical finding of these measurements is that the 800-nm pulse, at a specific delay relative to the two-color pulse, enhances the THz emission of the filament by as much as 30 times. Our measurements also confirm that for negative delays (the enhancement pulse arrives before the two-color pulse) the THz yield is suppressed significantly, as demonstrated previously for the case where both the two-color pulse and the enhancement pulse were centered at 800 nm [21,22,24]. Both of these findings are illustrated by plotting the THz yield of the filament as a function of the delay of the enhancement pulse relative to the two-color pulse.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The critical finding of these measurements is that the 800-nm pulse, at a specific delay relative to the two-color pulse, enhances the THz emission of the filament by as much as 30 times. Our measurements also confirm that for negative delays (the enhancement pulse arrives before the two-color pulse) the THz yield is suppressed significantly, as demonstrated previously for the case where both the two-color pulse and the enhancement pulse were centered at 800 nm [21,22,24]. Both of these findings are illustrated by plotting the THz yield of the filament as a function of the delay of the enhancement pulse relative to the two-color pulse.…”
supporting
confidence: 90%
“…Having established the two-color filament generation technique, many researchers are actively investigating ways to optimize or improve the THz output [14][15][16][17][18][19][20]. Of particular relevance to this work, several researchers have explored the idea of using additional pulses prior to the two-color pulse in order to introduce a preexisting plasma and alter the THz emission [21][22][23][24]. In one of these reports, Minami et al showed that a prepulse had the clear effect of suppressing the THz generation of the plasma generation pulse; concluding that depleted neutral populations diminished the efficiency of plasma THz generation [24].In another vein of investigation, THz yields were drastically improved using longer pump wave-lengths, so much that the losses incurred during conversion in an OPA to longer wavelengths are more than made up for in the THz generation [9,25].…”
mentioning
confidence: 99%
“…The temporal characteristics and corresponding mechanism in the gas phase have been widely investigated. 35,36 The results of nitrogen gas in our experiment are consistent with previous studies. The experimental evidence in Fig.…”
Section: Experimental Results and Analysissupporting
confidence: 92%
“…Generating THz waves via two-color laser focusing in a gas has overcome the problematic radiation properties of THz waves from a gas plasma. [15][16][17] In this scheme, linearly polarized THz waves are generated in the forward direction. This requires precise adjustment of the temporal deviation between the two pulses to match their phases.…”
mentioning
confidence: 99%